2021
DOI: 10.37506/ijphrd.v12i1.13877
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Application of Rational-Emotive Health Education for Stress Management in Teachers

Abstract: There is evidence that teachers encounter more stress than people in other professions. Stressors in teaching include students' misbehaviour, excess workload, and time pressure among others. Teachers in developing countries like Nigeria encounter additional stressors outside common job stressors. Stressors peculiar to teachers in developing countries include transportation issues, cultural challenges, and delays in payment of salary. High level of stress in teaching results to health problems, burnout, absente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 25 publications
2
2
0
Order By: Relevance
“…According to Ede et al, a component of REBT significantly improved parents' ability to control their stress when raising children with autism spectrum disorders. Furthermore, teachers' stress levels decreased significantly with rational-emotive health education, as reported in a previous report (Obiagu et al, 2021). Ogba et al (2020) reported that REOHC substantially decreased the subjective perceptions of stress at work as well as its external manifestations among the participants.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…According to Ede et al, a component of REBT significantly improved parents' ability to control their stress when raising children with autism spectrum disorders. Furthermore, teachers' stress levels decreased significantly with rational-emotive health education, as reported in a previous report (Obiagu et al, 2021). Ogba et al (2020) reported that REOHC substantially decreased the subjective perceptions of stress at work as well as its external manifestations among the participants.…”
Section: Discussionsupporting
confidence: 76%
“…After being exposed to REFHT, parents of children with autistic spectrum disorders showed a considerable improvement in their ability to manage parenting stress (Ede et al, 2020). This is consistent with a study, showing that rational-emotive health education significantly reduced stress in teachers (Obiagu et al, 2021). Ogba et al (2020) reported that REOHC significantly decreased the subjective perceptions of participants about the condition and its external manifestations.…”
Section: Stress Management Intervention For Secondary School Physics ...supporting
confidence: 84%
“…found that an aspect of REBT had a significant impact on parenting stress management among parents of children with autism spectrum disorders. Teachers' stress was found to be greatly reduced by rational-emotive health education (Obiagu et al, 2021). According to Ogba et al (2020), REOHC significantly reduced their subjective feelings and outward manifestations of stress at work.…”
Section: Discussionmentioning
confidence: 95%
“…Teachers' stress was shown to be greatly reduced by a rational-emotive health program (Obiagu et al, 2021). According to Ogba et al (2020), REBT significantly reduced subjective feelings and outward manifestations of stress at work.…”
Section: Introductionmentioning
confidence: 99%